Magnetic correlation functions in the slow and fast solar wind in the Eulerian reference frame - Weygand, James M. (2013)
Simultaneous multiple point measurements of the magnetic field from seven spacecraft are employed to estimate the Eulerian correlation function and decorrelation time scales in the near Earth solar wind for two different solar wind speed ranges. We find that the Eulerian decorrelation time scale differs significantly in the slow solar wind (<450 km/s), where quasi-two-dimensional turbulence dominates, and in the fast solar (>600 km/s) wind, where slab-type turbulence dominates. In slow solar wind, the decorrelation time is 215 ± 43 min, and in fast solar wind, the decorrelation time scale is 114 ± 23 min, which indicates that decorrelation times vary with the nature of the turbulence. The values reported here are comparable to estimates of decorrelation times based on a number of different models, but do not clearly support or refute any specific solar wind turbulence model. These results may be useful in magnetohydrodynamic modeling of the solar wind and can contribute to our understanding of solar and galactic cosmic ray diffusion in the heliosphere.